Quantization of the type II superstring in a curved six-dimensional background - Berkovits, Nathan [UNESP] (Elsevier, 2000)
A sigma model action with N = 2 D = 6 superspace variables is constructed for the Type II superstring compactified to six curved dimensions with Ramond - Ramond flux. The action can be quantized since the sigma model is linear when the six-dimensional space-time is flat. When the six-dimensional space-time is AdS 3 × S 3, the action reduces to one found earlier with Vafa and Witten. © 2000 Elsevier Science B.V. All rights reserved.